Analisis Tematik Terminologi Kepemimpinan dalam Hadis: Kajian Berbasis Metodologi Yūsuf al-Qarḍāwī - M. Maulana Fahmi; Ahmad Fudhaili (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
A leader is a highly important position that carries significant responsibility. In the books of Hadith, there are many terms that mean leader, such as Imām, Emīr, Khalīfah, Ḥakīm, Sulṭān, Mālik, Sayyid, Jabbār, Rāʿin, Qayṣar, Kisrā, and Aʿājim. The aim of this research is to understand leadership from the perspective of the Prophet’s hadiths. The study of leadership from the hadith perspective shows that there are various terms for leadership, and each term can also have multiple meanings. The approach used in this paper is the contemporary hadith approach of Yūsuf al-Qarḍāwī. This research employs a quantitative method based on library research, such as literature, books, journals, or other scientific works. The primary sources used are hadiths on leadership found in major hadith collections and the book Kayfa Nataʿāmal Maʿa al-Sunnah al-Nabawiyyah. Secondary sources include literature, books, journals, and other scientific works that discuss leadership. This research is linear in nature because it uses only one approach from a single field of study. It also briefly covers the meanings of leadership terms from dictionaries and various scholars.